Chemical and physical reinforcement behavior of dialdehyde nanocellulose in PVA composite film: A comparison of nanofiber and nanocrystal. (15th March 2020) - Lee, Hohyun; You, Jinhwa; Jin, Hyoung-Joon; Kwak, Hyo Won
Graphical abstract: Highlights: Nanocellulose modified with dialdehyde group shows the chemical reinforcing behavior of PVA composite films. Chemical network structure has greatly enhanced the thermal, mechanical and hydrophobic properties of PVA/DAC. In PVA/DCNF, physico-chemical structure appears simultaneously whereas PVA/DCNC occurs the chemical structure dominantly. Abstract: Nanocellulose can be categorized into cellulose nanofibers (CNFs) and cellulose nanocrystals (CNCs). CNFs and CNCs are oxidized by periodate oxidation to introduce dialdehyde groups, which can act as a crosslinking agent. Polyvinyl alcohol (PVA) is widely used in food packaging, however, it is vulnerable to aqueous environments. In this study, dialdehyde nanocellulose-reinforced PVA nanocomposite films were fabricated to enhance the water resistance. CNF and CNC were oxidized using varying amounts of sodium periodate and the selected fillers were designated as DCNF and DCNC, respectively. In the case of DCNF, physicochemical networking effect was induced to PVA, while DCNC showed only chemical network reinforcement effect. However, both PVA/DCNF and PVA/DCNC composite films have significantly improved vulnerabilities in moisture environment compared to PVA films. These results indicate that while physical network structures are important, the chemically formed network structures can play a crucial role in enhancing the water resistance of PVA films.